Building blocks of consciousness: Revealing the shared, hidden depths of our biological heritage - Juri van den Heever; Chris Jones (HTS Teologiese Studies/Theological Studies, 2020)
Human consciousness has been a hard problem for thousands of years and, in the course of time, variously interpreted and often too narrowly defined. As a result, the possibility of animal consciousness, sentience or even the possibility that animals can experience pain, received no, or very little, attention. Driven by the trope that animals lack the basic neural attributes to even experience pain, humans have seriously endangered the natural existence of untold multitudes of sentient organisms. However, humans are not the only conscious organisms on the planet, as suggested by a variety of research results, attesting to the fact that even lower vertebrates possess sentience and feel pain. Multiple research findings have now stressed the need for a phylogenetic approach to consciousness, which, in the long run, will have extensive theological implications. Succinctly put, these findings indicate that we live in a world of minds, and that only some of them are human.